Tubacin prevents neuronal migration defects and epileptic activity caused by rat Srpx2 silencing in utero - Manal Salmi; Nadine Bruneau; Jennifer Cillario; Natalia Lozovaya; Annick Massacrier; Emmanuelle Buhler; Robin Cloarec; Timur Tsintsadze; Françoise Watrin; Vera Tsintsadze; Céline Zimmer; Claude Villard; et al. (2013)
Altered development of the human cerebral cortex can cause severe malformations with often intractable focal epileptic seizures and may participate in common pathologies, notably epilepsy. This raises important conceptual and therapeutic issues. Two missense mutations in the sushi repeat-containing protein SRPX2 had been previously identified in epileptic disorders with or without structural developmental alteration of the speech cortex. In the present study, we aimed to decipher the precise developmental role of SRPX2, to have a better knowledge on the consequences of its mutations, and to start addressing therapeutic issues through the design of an appropriate animal model. Using an in utero Srpx2 silencing approach, we show that SRPX2 influences neuronal migration in the developing rat cerebral cortex. Wild-type, but not the mutant human SRPX2 proteins, rescued the neuronal migration phenotype caused by Srpx2 silencing in utero, and increased alpha-tubulin acetylation. Following in utero Srpx2 silencing, spontaneous epileptiform activity was recorded post-natally. The neuronal migration defects and the post-natal epileptic consequences were prevented early in embryos by maternal administration of tubulin deacetylase inhibitor tubacin. Hence epileptiform manifestations of developmental origin could be prevented in utero, using a transient and drug-based therapeutic protocol.